Pengaruh Store Atmosphere dan Service Quality terhadap Kepuasan Konsumen Rumah Makan Hj.Ocoh Sunda & Seafood Tasikmalaya - Rosidah Khoerunnasa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine the effect of store atmosphere and service quality simultaneously or partially on customer satisfaction of Restoran Hj.Ocoh Sunda & Seafood Tasikmalaya. The research method used is a quantitative method with a survey approach. The sample in this study amounted to 100 respodents. Data collection wa carried out using a questionnaire. The data analysis used is multiple regression analysis. The results of this study indicate that store atmosphere and service quality simultaneously have a significant effect on customer satisfaction. Partially, store atmosphere has a significant effect on customer satisfaction. Partially, service quality has a significant effect on customer satisfaction.